Caring for children with spinal muscular atrophy in Greece: parents' and caregivers' experience with the healthcare system - Souliotis, Kyriakos; Golna, Christina; Tzavara, Chara; Vasileiadi, Christiana; Golnas, Pavlos; Ntokou, Aikaterini; Binou, Kornilia; Karras, Antigone (Frontiers in Health Services, 2025)
IntroductionSpinal muscular atrophy (SMA) is a rare disease characterized by challenges in its management both for patients and parents/caregivers. In Greece, these challenges are exacerbated by the lack of an integrated SMA patient pathway. This survey mapped the experiences of parents of SMA pediatric patients with the Greek healthcare system, highlighting the actual pathway, its impact on quality of life, and associated financial burden.MethodsParents of children living with SMA, who were members of MDA Hellas, a non-profit organization for people with neuromuscular diseases in Greece, were invited to complete a novel online questionnaire, prepared in collaboration with the Health Policy Institute, a non-profit research organization specializing in health policy evaluation and design. The survey ran from May to September 2023. The results were analyzed using SPSS V26.0.ResultsForty-four parents participated in the survey, with a mean age of 43.2 years. In the absence of universal prenatal or newborn screening, parents were the first to recognize any symptoms in the majority (73.5%) of cases. A total of 38.6% of parents had to travel from their place of residence to receive a diagnosis for their child. More than half had to pay out-of-pocket for diagnosis-related services. Parents shouldered additional treatment services and assistive aids' costs in excess of 300 euros a month. The majority reported feelings of agony and fear (90.9%) and guilt (25%) upon receiving the diagnosis. The average PedsQol score was 67 (SD = 15.8), whereas Zarit scores confirmed a higher burden for caregivers of children with graver SMA types.ConclusionThis survey details the concerns and needs and quantifies SMA burden on parents/caregivers of children with SMA in Greece to inform health policy advocacy. Such advocacy should be translated into a national action plan with a focus on integrating care organization and delivery options.